Revascularization for Left Anterior Descending Artery Stenosis: A Review of the Evidence That Supports Practice. Issue 3 (May 2016) - Kinnaird, Tim; Anderson, Richard; Ossei-Gerning, Nicholas; Mamas, Mamas A.; Ludman, Peter; Moat, Neil
Abstract : Disease of the proximal left anterior descending (LAD) artery is a common pathological finding often combined with disease in other coronary arteries. In this article, we review specifically the evidence (and the guidelines arising from the data) for lesions isolated to the proximal LAD only. Critical review of the data reveals limitations with few trials that reflect contemporary practice. Much of the data are observational rather than from randomized trials, and therefore subject to bias. We identified 2 randomized trials of drug-eluting stents versus left internal mammary artery grafting for isolated lesions of the proximal LAD. One reported no difference in major adverse cardiovascular events, but at an early timepoint (6 months), which is likely to be too early to reveal treatment differences. In the second trial, target lesion revascularization excess was noted in the drug-eluting stent arm. Therefore, at the current time, there are little data available to inform interventional cardiologists as to the best revascularization strategy for isolated lesions of the proximal LAD. Further randomized, controlled trials are needed.